2013
DOI: 10.1002/hed.23417
|View full text |Cite
|
Sign up to set email alerts
|

Heightened risk of second primary carcinoma of the head and neck following cervical neoplasia

Abstract: This study demonstrates that women with cervical cancer were almost 7 times more likely to develop head and neck cancer compared to the general female population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
(64 reference statements)
1
4
0
1
Order By: Relevance
“…However, in most countries, men are more exposed to unhealthy lifestyles and carcinogenic factors such as alcohol, tobacco and diet, which have been associated with the pathogenesis of the disease [1,21]. In general, age groups that were most affected by ODE and OSCC correspond to the 5th and 7th decade, respectively, and coincides with that reported in the literature [22,23]. This difference could be due to the fact that for the development of an OSCC, the action of carcinogens that provoke non-lethal mutations in the DNA for a long period of time is necessary so that the first cell that multiplies autonomously and uncontrolled will originate into the neoplastic mass.…”
Section: Comparing the Immuno-expression Of Endothelial Markers In Nosupporting
confidence: 78%
“…However, in most countries, men are more exposed to unhealthy lifestyles and carcinogenic factors such as alcohol, tobacco and diet, which have been associated with the pathogenesis of the disease [1,21]. In general, age groups that were most affected by ODE and OSCC correspond to the 5th and 7th decade, respectively, and coincides with that reported in the literature [22,23]. This difference could be due to the fact that for the development of an OSCC, the action of carcinogens that provoke non-lethal mutations in the DNA for a long period of time is necessary so that the first cell that multiplies autonomously and uncontrolled will originate into the neoplastic mass.…”
Section: Comparing the Immuno-expression Of Endothelial Markers In Nosupporting
confidence: 78%
“…Most Asian studies were conducted in or by single institutes and had limited populations. 4 , 8 , 25 , 30 , 31 A study published in 2012 based on the Taiwan Cancer Registry that enrolled 52,972 patients also found increased SIRs in patients with cervical cancer. 2 However, only the age of patients, registry date, and sites of cancer were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that tobacco and/or alcohol induced precancerous fields of the upper aerodigestive tract may be amplified by local HPV infection . A recent Australian study concluded that amongst females with a history of cervical cancer, there was a greater risk of developing oral cancer, particularly of the oropharynx, compared to the general female population . Given the implementation of a national HPV vaccination programme, and the anticipated decline in cervical cancer incidence, it is anticipated that the incidence of oropharyngeal cancers will also decrease in the long term.…”
Section: Discussionmentioning
confidence: 99%